Paths of Heritable Mitochondrial DNA Mutation and Heteroplasmy in Reference and gas-1 Strains of Caenorhabditis elegans - Wernick, Riana I.; Estes, Suzanne; Howe, Dana K.; Denver, Dee R. (Frontiers in Genetics, 2016)
Heteroplasmy—the presence of more than one mitochondrial DNA (mtDNA) sequence type in a cell, tissue, or individual—impacts human mitochondrial disease and numerous aging-related syndromes. Understanding the trans-generational dynamics of mtDNA is critical to understanding the underlying mechanisms of mitochondrial disease and evolution. We investigated mtDNA mutation and heteroplasmy using a set of wild-type (N2 strain) and mitochondrial electron transport chain mutant (gas-1) mutant Caenohabditis elegans mutation-accumulation (MA) lines. The N2 MA lines, derived from a previous experiment, were bottlenecked for 250 generations. The gas-1 MA lines were created for this study, and bottlenecked in the laboratory for up to 50 generations. We applied Illumina-MiSeq DNA sequencing to L1 larvae from five gas-1 MA lines and five N2 MA lines to detect and characterize mtDNA mutation and heteroplasmic inheritance patterns evolving under extreme drift. mtDNA copy number increased in both sets of MA lines: 3-fold on average among the gas-1 MA lines and 5-fold on average among N2 MA lines. Eight heteroplasmic single base substitution polymorphisms were detected in the gas-1 MA lines; only one was observed in the N2 MA lines. Heteroplasmy frequencies ranged broadly in the gas-1 MA lines, from as low as 2.3% to complete fixation (homoplasmy). An initially low-frequency (<5%) heteroplasmy discovered in the gas-1 progenitor was observed to fix in one gas-1 MA line, achieve higher frequency (37.4%) in another, and be lost in the other three lines. A similar low-frequency heteroplasmy was detected in the N2 progenitor, but was lost in all five N2 MA lines. We identified three insertion-deletion (indel) heteroplasmies in gas-1 MA lines and six indel variants in the N2 MA lines, most occurring at homopolymeric nucleotide runs. The observed bias toward accumulation of single nucleotide polymorphisms in gas-1 MA lines is consistent with the idea that impaired mitochondrial activity renders mtDNA more vulnerable to this type of mutation. The consistent increases in mtDNA copy number implies that extreme genetic drift provides a permissive environment for elevated organelle genome copy number in C. elegans reference and gas-1 strains. This study broadens our understanding of the heteroplasmic mitochondrial mutation process in a multicellular